CO and CO2 adsorption mechanism in Fe(pz)[Pt(CN)4] probed by neutron scattering and density-functional theory calculations. Issue 16 (4th April 2023) - Fernández-Blanco, Ángel; Piñeiro-López, Lucía; Jiménez-Ruiz, Mónica; Rols, Stephane; Antonio Real, José; Sanchez Costa, Jose; Poloni, Roberta; Rodríguez-Velamazán, J. Alberto
Abstract : We study the binding mechanism of CO and CO2 in the porous spin-crossover compound Fe(pz)[Pt(CN)4 ] by combining neutron diffraction (ND), inelastic neutron scattering (INS) and density–functional theory (DFT) calculations. Abstract : We study the binding mechanism of CO and CO2 in the porous spin-crossover compound Fe(pz)[Pt(CN)4 ] by combining neutron diffraction (ND), inelastic neutron scattering (INS) and density–functional theory (DFT) calculations. Two adsorption sites are identified, above the open-metal site and between the pyrazine rings. For CO adsorption, the guest molecules are parallel to the neighboring gas molecules and perpendicular to the pyrazine planes. For CO2, the molecules adsorbed on-top of the open-metal site are perpendicular to the pyrazine rings and those between the pyrazines are almost parallel to them. These configurations are consistent with the INS data, which are in good agreement with the computed generalized phonon density of states. The most relevant signatures of the binding occur in the spectral region around 100 cm −1 and 400 cm −1 . The first peak blue-shifts for both CO and CO2 adsorption, while the second red-shifts for CO and remains nearly unchanged for CO2 . These spectral changes depend both from steric effects and the nature of the interaction. The interpretation of the INS data as supported by the computed binding energy and the molecular orbital analysis are consistent with a physisorption mechanism for both gases. This work shows the strength of the combination of neutron techniques and DFT calculations to characterize in detail the gas adsorption mechanism in this type of materials.